2021
DOI: 10.3390/cancers13153650
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as a Potential New Preventive Approach in the Transition from Asymptomatic to Symptomatic Multiple Myeloma Disease

Abstract: Multiple myeloma (MM) is a hematological malignancy characterised by proliferation of clonal plasma cells (PCs) within the bone marrow (BM). Myelomagenesis is a multi-step process which goes from an asymptomatic phase, defined as monoclonal gammopathy of undetermined significance (MGUS), to a smouldering myeloma (SMM) stage, to a final active MM disease, characterised by hypercalcemia, renal failure, bone lesions anemia, and higher risk of infections. Overall, microRNAs (miRNAs) have shown to significantly imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 107 publications
0
18
0
Order By: Relevance
“…Low levels of let-7e, miR-223-3p and miR-744 were associated with shorter remission and OS in MM patients [ 147 , 148 ], while up-regulation of miR-720 and miR-1246 correlated with shorter PFS data [ 149 ].…”
Section: Clinical Applications Of Mirnas Focusing On Hematological Ma...mentioning
confidence: 99%
“…Low levels of let-7e, miR-223-3p and miR-744 were associated with shorter remission and OS in MM patients [ 147 , 148 ], while up-regulation of miR-720 and miR-1246 correlated with shorter PFS data [ 149 ].…”
Section: Clinical Applications Of Mirnas Focusing On Hematological Ma...mentioning
confidence: 99%
“…Several studies support the function of miRNA as tumour suppressors [ 55 ], e.g., miR-34 represses tumour progression through epithelial-mesenchymal transition (EMT) via EMT-transcription factors when dysregulated via the synergistic effect of the p53 tumor suppressor gene and some important signal pathways. Several invitro studies on various cancer cell lines found that through different signalling pathways downregulation of the family of miR-34 can lead to colon, prostate, lung, osteosarcoma, and other types of cancers [ 54 , 55 , 56 , 57 , 58 , 59 ]. Similarly, Pichiorri et al found the overexpression of miR-106b∼25 cluster, miR-181a and b and miR-21 in MM cell lines leading to the tumour compared to normal cell controls thus acting as an oncogene when two miRNA cluster.…”
Section: Mirnas—biogenesis Biochemistry and Functionsmentioning
confidence: 99%
“…Similarly, Pichiorri et al found the overexpression of miR-106b∼25 cluster, miR-181a and b and miR-21 in MM cell lines leading to the tumour compared to normal cell controls thus acting as an oncogene when two miRNA cluster. In contrast, miRNA-106b, miRNA-181a and b were found to be deregulated, thus acting as tumour suppressors [ 58 ].…”
Section: Mirnas—biogenesis Biochemistry and Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although gene expression profiles focusing on coding genes provide valuable insight into cell development and malignant transformation, protein-coding genes account for less than 3% of the human genome, with over 70% of the genome being transcribed into non-coding RNAs (ncRNAs) [11], leading to intensive investigations into potential functional roles for ncRNAs. Indeed, both small non-coding micro-RNAs (miRNAs) and long non-coding RNAs (lncRNAs) have been shown to play important roles in many processes including B cell development and malignancy including multiple myeloma (MM), a plasma cell dyscrasia (reviewed in [12][13][14][15][16]). Furthermore, there is a growing recognition of the integral role that ncRNAs play in both Ig gene rearrangement and class switch recombination [17][18][19], underscoring the need to more completely identify patterns of ncRNA expression that occur during B cell activation, proliferation, and differentiation into PCs.…”
Section: Introductionmentioning
confidence: 99%